PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM TRANSAKSI PEMILIKAN RUMAH DI KABUPATEN MALANG - Mahmudy, Davy Ananda W.S. (Jurnal Cakrawala Hukum, 2016)
Issues relating to the legal protection of the consumers in homeownership transactions in Malang regency are related to civil law and administrative law. Technical for this matter involves the parties, Notary and the Bank, especially the State Savings Bank. technically, that the transfer of rights (credit oper), must be done through Notary’s office. The main factor is the existence of the obstacles due to the debtor, and prospective new debtors who cannot be reunited and present together to the Bank. Both have transferred rights under their own hands. Of course without notifying the State Savings Bank. In accordance with the above, it is relevant that the bank should immediately take care and deal with the State Savings Bank. The goal is to know with certainty the credit position of the debtor. It is deemed necessary to avoid or anticipate the emergence of problematic credit transfers in the future. The Bank must proactively conduct the necessary verifications to the entire process and documents required.